Peranan Kewirausahaan Dalam Meningkatkan Ekonomi Kreatif Dan Inovatif - Purwaningsih, Dewi (Rifa'Institute, 2024)
Entrepreneurship is a major driver of innovation, economic growth, and global competitiveness. Its main role is to create new ideas, create jobs, and drive improvements in the quality of products and services. Entrepreneurship is the key to building a strong, sustainable economy centered on creativity and innovation. This study aims to provide a new understanding of entrepreneurship in improving the creative and innovative economy and its relationship to the progress of the Indonesian economy. The author uses a qualitative descriptive research method to write this scientific article, and is taken from various journal articles and the author Compiles by analyzing various references to the articles. The results of this study indicate that entrepreneurship has a role in encouraging and improving the creative and innovative economy. Entrepreneurship can encourage economic growth, increase income, and the formation of an independent and empowered society to encourage the creative industry in developing creativity, innovation, and its development. An Entrepreneur is a driving force in generating new ideas, creative and innovative goods and services.